Analisis Perbandingan Struktur Tata Bahasa Jerman dan Bahasa Indonesia - Daulay, Jihan Nur Alfiana; Veronika, Meilani; Manik, Bertuah; Azizah, Nurul (UNIVERSITAS SERAMBI MEKKAH, 2025)
This research aims to analyze the comparison of German and Indonesian grammatical structures. This research uses the contrastive analysis method to compare the grammatical structures of the two languages. The data collection technique was conducted through literature study and document analysis, in which the researcher collected examples of sentences and grammatical structures from both languages. The results show that the grammatical structures of German and Indonesian have some similarities and differences. The similarity between the two languages is the use of the sentence structure S-P-O (Subject-Predicate-Object) or in German S-V-O (Subject-Verb-Object), while the difference between the two languages is the use of cases and articles on nouns in German and the absence of cases and articles on nouns in Indonesian. This research is expected to contribute to the development of grammar theory and the learning of German and Indonesian.